A new locality of Solidago ×niederederi Khek (Asteraceae) in Poland - Pliszko, Artur (Biodiversity: Research and Conservation, 2013)
Solidago ×niederederi is a natural hybrid between S. canadensis and S. virgaurea, which occurs sporadically in synanthropic habitats together with the parental species. The hybrid was reported from seven countries in Central and Northern Europe and its presence emphasizes the invasive character of S. canadensis. A new locality of the hybrid was found in Mieruniszki village in the Zachodniosuwalskie Lakeland in NE Poland in 2011 (ATPOL square: FB06). Solidago ×niederederi grew on fallow land, at the edge of planted birchen shrubbery and its population comprised two small clumps. Current data suggest that the hybrid is a casual alien in the Polish flora, however, it has the potential to become established by clonal growth or restricted sexual reproduction.